Flexible electrochromic fiber with rapid color switching and high optical modulation - Zhu, Tianxue (2021)
Though flexible electrochromic devices have shown huge potential application in the fields of safety warning, display and smart windows, limited attention was paid on preparing flexible electrochromic fiber because of the difficulty in fabricating the multilayer electrochromic device structure in one-dimensional form. In this study, a flexible electrochromic nylon fiber based on Ag nanowires (NWs)/PEDOT:PSS/WO3 nanoparticles (NPs) (PEDOT:PSS = poly(3,4-ethylenedioxythiophene):polystyrenesulfonic acid) is successfully fabricated, delivering rapid color switching (2.5 and 9 s for bleaching and coloration) and high optical modulation (65.5% at 633 nm), and sustainable to repeated mechanical deformations. Ag NWs, PEDOT:PSS and WO3 NPs were dip-coated on the nylon fiber, resulting in an electrochromic fiber electrode with stable fiber resistance of 50–100 Ω/10 cm, which can withstand mechanical deformation against 300 times of bending cycles with bending radius of 0.5 cm, and sustain 30 times of tape-peeling. During the galvanostatic tests, the capacitance of the electrochromic electrode can maintain 70% of the initial value even after 5,000 times of charge-discharge cycles. Even in knotted shape, the fiber still shows excellent color contrast. This study provides a novel method to construct flexible electrochromic fiber and pave the way for the development of flexible optoelectronic devices, such as flexible and wearable displays. [Figure not available: see fulltext.]